Reclaiming Human Rights: Afghan Women Journalists’ Struggle under Taliban Governance (2021–2024) - Dehqanyar, Aghamah (Universitas Islam Indonesia, 2026)
Since the Taliban took power again in August 2021, women's rights in Afghanistan have gotten a lot worse. Women journalists have had some of the worst limitations. This article analyzes the legal and gender-based violations perpetrated against Afghan women journalists from 2021 to 2024, emphasizing Afghanistan's responsibilities under the International Covenant on Civil and Political Rights (ICCPR) and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). Utilizing a descriptive-analytical and doctrinal legal technique, the study references international human rights instruments, United Nations reports, and recent academic literature. The analysis employs a Human Rights–Based Approach, augmented by perspectives from feminist legal theory, to evaluate the constitutionality of Taliban decrees governing media participation, employment, movement, and expression. The results show that these actions are systemic discrimination against women and violate basic rights, such as the right to work, freedom of speech, equality before the law, and the ability to take part in public life. International monitoring agencies have done a lot of work to document these transgressions, but the current accountability systems have not been very successful in dealing with them. The essay concludes that Afghan women journalists need better treaty-based oversight, acknowledgment of gender persecution under international law, and ongoing political and financial assistance for media groups run by women who are living in exile.